2012
DOI: 10.4236/health.2012.410131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of job satisfaction on burnout among physicians: A survey study in urban public medical institutions in Hubei province, China

Abstract: Objectives: Chinese physicians are being loaded with the enormous psychological pressure and so tend to be susceptible to burnout. Little is known on the relationship between job satisfaction and burnout for physicians from urban public medical institutions. We aim to describe the degree of burnout and evaluate the impact of job satisfaction on burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another study indicated that dissatisfaction with the practice specialty and with patient relationships were important predictors of burnout 17 . Other variables that have been related to burnout include work environment satisfaction, job rewards satisfaction, and organizational management satisfaction 18 . In our multivariate analysis, only practice satisfaction and income satisfaction were significantly associated with burnout, indicating that the level of gratification based on the responsibilities performed as a rheumatologist and the income received in this specialty constitute the most important among the different dimensions of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that dissatisfaction with the practice specialty and with patient relationships were important predictors of burnout 17 . Other variables that have been related to burnout include work environment satisfaction, job rewards satisfaction, and organizational management satisfaction 18 . In our multivariate analysis, only practice satisfaction and income satisfaction were significantly associated with burnout, indicating that the level of gratification based on the responsibilities performed as a rheumatologist and the income received in this specialty constitute the most important among the different dimensions of satisfaction.…”
Section: Discussionmentioning
confidence: 99%